Fabrication of patterned thermoplastic microphases between composite plies by inkjet printing. (June 2015) - Zhang, Yi; Stringer, Jonathan; Grainger, Richard; Smith, Patrick J; Hodzic, Alma
We report on the pioneering application of inkjet printing in depositing patterned thermoplastic microphases between composite plies and the beneficial effect of the printed thermoplastic on the interlaminar fracture toughness of carbon fibre-reinforced polymer laminates. Double-cantilever beam test and short-beam shear test were employed to investigate the mechanical performances of the engineered composites. The results from this work revealed that by printing thermoplastic poly(ethylene glycol) and poly(methyl methacrylate) between the carbon fibre-reinforced polymer plies, mode I interlaminar fracture toughness (GIc ) is noticeably enhanced, whilst the shear strength has also been preserved. Scanning electron microscopy was used to investigate the fracture surfaces generated during the double-cantilever beam test. The microscopic addition of the thermoplastic polymers (approximately 0.015 wt%) did not increase the weight of the composites significantly, which compares favourably to other conventional toughening methods.